Why not treat human cancer with interleukin-1 blockade? - Dinarello, Charles A. (Springer US, 2010)
The clinical successes of targeting angiogenesis provide a basis for trials of interleukin-1 (IL-1) blockade and particularly anti-IL-1β as an add-on therapy in human metastatic disease. In animal studies for over 20 years, IL-1 has been demonstrated to increase adherence of tumor cells to the endothelium in vitro, and administration of IL-1 to mice increases the number of metastatic colonies and tumor growth. Importantly, reducing endogenous IL-1 activity, particularly IL-1β, with the naturally occurring IL-1 receptor antagonist (IL-1Ra) reduces both metastasis as well as tumor burden. Inhibition of IL-1 activity prevents in vivo blood vessel formation induced by products released from hypoxic macrophages or vascular endothelial cell growth factor itself. Mice deficient in IL-1β do not form blood vessels in matrigels embedded with vascular endothelial cell growth factor or containing products of macrophages. Recombinant IL-1Ra (anakinra) has been administered to over 1,000 patients with septic shock resulting in a consistent reduction in all-cause 28-day mortality. Approved for treatment of rheumatoid arthritis, anakinra has a remarkable safety record. Anakinra resulted in decreased blood vessels in the pannus of affected joints in patients with rheumatoid arthritis. Neutralizing monoclonal antibodies to IL-1β and a soluble receptor to IL-1 are approved for treating chronic inflammatory diseases. Given the availability of three therapeutic agents for limiting IL-1 activity, the safety of blocking IL-1, and the clear benefit of blocking IL-1 activity in animal models of metastasis and angiogenesis, clinical trials of IL-1 blockade should be initiated, particularly as an add-on therapy of patients receiving antiangiogenesis-based therapies.